DC shunt motor speed control methods using MATLAB/Simulink and interfaced with graphic user interface (GUI): article / Muhammad Najmi Hamzah - Hamzah, Muhammad Najmi (Universiti Teknologi MARA (UiTM), 2010)
This paper presents simulation model of DC shunt motor speed control method using MATLAB/Simulink software and interfaced with Graphical User Interface (GUI) software. In this paper, DC shunt motor speed is controlled by armature resistance, field resistance and armature voltage speed control. Its torque-speed characteristics are observed and analyzed. The simulation model will enable an easier understanding for undergraduate electric machinery courses on bow the actual machine works and ease of use of the program using MATLAB/GUI designed program.